Aluminum matrix composites reinforced with multi-walled boron nitride nanotubes fabricated by a high-pressure torsion technique. (25th December 2015) - Xue, Yanming; Jiang, Baozhen; Bourgeois, Laure; Dai, Pengcheng; Mitome, Masanori; Zhang, Chao; Yamaguchi, Maho; Matveev, Andrei; Tang, Chengchun; Bando, Yoshio; Tsuchiya, Koichi; Golberg, Dmitri
ABSTRACT: Aluminum matrix composites loaded with various fractions of multi-walled, well-structured boron nitride nanotubes (BNNTs), up to 5 wt.% fractions, were fabricated using powder constituents by means of a high pressure torsion technique (HPT) at room temperature under 5 GPa pressurization. Transient ultrathin amorphous-like layers, with a thickness of 2–5 nm, composed of Al(BNO) phases, which formed under severe plastic deformation and developed under further heat treatments of the composites at 350 °C and 450 °C, were detected at the interfacial regions between Al grains and tightly embracing them BN layers. Room temperature hardness and tensile tests on fabricated composites before and after heat treatments were conducted. The highest value of room temperature tensile strength was obtained on Al-5 wt.% BNNT samples annealed at 450 °C, that reached up to 420 MPa, thus exhibiting more than a doubled increase in strength compared to HPT-fabricated pure Al samples under identical compacting conditions. Graphical abstract: Highlights: Al-matrix composites reinforced with 1-5 wt.% of BN nanotubes (BNNTs) were fabricated via a high-pressure torsion (HPT) Amorphous-like Al(BNO) layers (2-5 nm thick) were detected between Al nanocrystalline grains and BNNTs embracing them Hardness and tensile strength of HPT-Al/BNNTs composites significantly increased compared to pure HPT-Al samples Tensile strength reached 420 MPa for a heat-treated Al-5 wt.% BNNT composite